A History of the Convention on International Trade in Endangered Species of Wild Fauna and Flora Implementation in Nepal - Sagar Dahal; Joel T. Heinen (Diversity)
The Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) is a conservation and trade convention regulating international trade in wild species listed under its various appendices. Party nations are required to have designated scientific and management authorities to administer CITES and, ideally, domestic enabling legislation for proper implementation. However, the complexity of the convention makes it difficult to implement in resource-constrained nations that lack expertise and commitment. Apart from the lack of resources and expertise in much of the global south, hurdles to CITES implementation arise from delays in the formation of necessary legislation, apathy in enforcing the legislation, and the gatekeeping of resources by leading government agencies. Nepal has a long and well-documented history of wildlife conservation and is party to most major global environmental conventions, although it has frequently lacked the ability to implement them fully. Recently, Nepal has formulated domestic policies and developed institutions supporting biodiversity conservation but still refrains from formulating and implementing some provisions. After a long history of only partial (at best) compliance, Nepal enacted domestic CITES-implementing legislation, the CITES Act of 2017, with progressive provisions for enforcement, wildlife farming, and resource utilization and conservation. Here, we used a mixed methods research approach involving published and gray literature reviews and key informant interviews with concerned stakeholders to understand the workings and modality of authorities under the 2017 Act. We explore its nuances and discuss potential challenges for its implementation over time. Though the new policy has many positive aspects in that it is progressive in shifting away from more classical, strict protection, we found that there are still shortcomings within national administrative structures and a lack of policy that coordinates and informs different government offices of their responsibilities and how they interface under the current federal system. This has resulted in ongoing obstacles to achieving fuller CITES implementation to date and, in some cases, also inhibits sustainable uses of biodiversity.